2022
DOI: 10.1101/2022.10.21.22281355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic contributions to clinical risk prediction of cardiovascular disease

Abstract: Background and AimsCardiovascular disease (CVD) is among the leading causes of death worldwide. Therefore, it is important to identify CVD risk as early as possible and to translate this knowledge into effective preventative strategies. Here, ASSIGN – a cardiovascular risk calculator recommended for use in Scotland – was examined in tandem with epigenetic and proteomic features in risk prediction models in 12,790 participants in the Generation Scotland cohort.MethodsPreviously generated DNA methylation-derived… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…methylation data acquired as part of STRADL) was used to generate signatures for 17 protein markers of brain health [41]. Finally, Chybowska et al demonstrated the utility of methylation-derived EpiScores and composite measures of these scores to identify CVD risk, independent of traditional risk factors [42].…”
Section: Data Resource Usementioning
confidence: 99%
“…methylation data acquired as part of STRADL) was used to generate signatures for 17 protein markers of brain health [41]. Finally, Chybowska et al demonstrated the utility of methylation-derived EpiScores and composite measures of these scores to identify CVD risk, independent of traditional risk factors [42].…”
Section: Data Resource Usementioning
confidence: 99%
“…DNAm-based epigenetic scores (EpiScores) for blood proteins have been found to serve as markers of incident diseases (16) and augment clinically-used risk factors for risk stratification (17,18). DNAm reflects the body’s chronic response to low-grade inflammation, environmental and biological exposures (19–21).…”
Section: Introductionmentioning
confidence: 99%
“…Both protein markers have also been found to associate with vascular brain injury, poorer neurocognitive performance and incident dementias (14,15). DNAm-based epigenetic scores (EpiScores) for blood proteins have been found to serve as markers of incident diseases (16) and augment clinically-used risk factors for risk stratification (17,18). DNAm reflects the body's chronic response to low-grade inflammation, environmental and biological exposures (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%